Leveraging Machine Learning For The Early Identification And Intervention Of Pediatric Mental Health Disorders: An Interdisciplinary Approach. - Safdar B, Mohamed; S., Pandiarajan (Journal of Neonatal Surgery, 2025)
The rising prevalence of mental health issues among children necessitates early identification and timely intervention, as traditional diagnostic methods, though standardized, often prove time-consuming and may delay appropriate treatment. This delay underscores the urgent need for innovative, technology-driven solutions. Machine learning (ML) has emerged as a powerful tool capable of analyzing vast and complex datasets to identify subtle, often overlooked patterns associated with mental health disorders. This study explores the potential of ML in enhancing the early detection of pediatric mental health conditions by improving diagnostic accuracy and reducing intervention delays. It further examines the practical utility of ML in processing emotional, behavioral, and cognitive indicators to recognize early warning signs. In doing so, the study highlights the transformative capacity of ML in augmenting existing diagnostic frameworks. However, it also addresses the critical ethical considerations involved, particularly concerning data privacy, algorithmic transparency, and the minimization of inherent biases. The integration of ethical safeguards is emphasized as essential to ensuring the responsible deployment of these technologies. This balanced approach promotes trust and efficacy in ML-based systems. Ultimately, the study illustrates how ML can reshape pediatric mental health care by offering faster, more accurate, and ethically grounded interventions that respond to the unique needs of children in distress.